Assertive communication as a condition for meaningful learning (Research, Society and Development, 2022)
This is an excerpt from the master's research of the PPGEn UNIC/IFMT Program, already completed and developed with the objective of understanding the relevance of communication as a driver of teacher-student relationships for Meaningful Learning in the context of elementary education. This is a case study in which scripted semi-structured interviews are used as a data collection instrument for data interpretation through content analysis. Interviews were conducted with teachers and students from 2 (two) public elementary schools in Várzea Grande, Mato Grosso. In the present article, the analyzes of the reports obtained by the students were considered. The research results suggest that confident communication and focused on the teacher-student relationship needs to be prioritized as a relevant tool in teaching and used by teachers for their own benefit, making students feel important and, thus, develop their self-esteem, resulting in greater interest in the subject and greater intellectual development. In the daily classroom, communication is essential for the performance of the interaction processes existing between teacher and student. For the students interviewed, this is only possible if the teacher makes space for the student to express himself, and it is through such an attitude that gains related to self-knowledge and self-confidence are provided, thus leading the student to acquire autonomy.